Structure of redispersible SnO2 nanoparticles - Brito, GES; Fischer, H.; Craievich, A. F.; Goncalves, R. R.; Ribeiro, SJL (Kluwer Academic Publ, 2003)
Suspensions of undoped SnO2 nanoparticles and containing Eu3+ ions were prepared by a sol-gel procedure. Using the classical synthesis method ( precipitation), the particles tend to grow by a coarsening process in order to minimize the surface free energy. This effect can strongly be reduced by the addition of an amide and surfactant during the synthesis, which decreases the surface free energy of the colloidal particles. These additives promote the formation of powders composed of very small primary particles formed by a crystallite of 10 Angstrom, and exhibit good redispersion properties. The local and long order structures of the redispersible powder were studied by X-rays absorption spectroscopy at Sn L-I edge and X-rays diffraction, respectively. The structure of the colloidal aggregates in suspension was investigated by small angle X-rays scattering (SAXS). SAXS results indicate the sol are composed by a polidisperse system of hard spheres resulting of agglomeration of the primary particles and their size increasing by agglomeration for progressively higher Eu3+ content.
Keywords: SnO2 nanoparticles; SAXS; EXAFS; XRD